Efeito antinociceptivo, antiinflamatório e antioxidante da Aloe saponaria Haw em modelos de queimadura em ratos - Silva, Mariane Arnoldi da (2013)
In Brazil, the plant Aloe saponaria Haw, popularly known as babosa pintadinha , has been empirically used for its potential effect on skin burn injury, there are no scientific data confirming its popular use. Thus, the aim of the present study was to investigate the effects of Aloe saponaria on nociceptive, inflammatory and antioxidants parameters in rat models of thermal injury. Adult male Wistar rats were subjected to a thermal injury (immersion in water at 70 or 37 ºC, respectively, for 5 or 8 seconds) or sunburn (induced by UVB irradiation), in both experiments the animals were anesthetized. Burned animals were topically treated with vehicle (base cream), sulfadiazine 1% (positive control) or Aloe saponaria cream (0.3-30%) once a day for 2 or 6 days. Each day, 30 min before the treatment, we measured nociceptive (static and dynamic mechanical allodynia, thermal allodynia and spontaneous pain), inflammatory (paw edema) parameters and oxidative stress (increases in H2O2, protein carbonyl levels and lipid peroxidation and a decrease in thiol content). In addition, was also evaluated infiltration of leukocytes in injured tissue (for histology or by measuring the activity of myeloperoxidase (MPO), N - acetyl - glucosaminidase (NAGase) and eosinoperoxidase (EPO), for neutrophils, macrophages, and eosinophils infiltration, respectively), were also determined 2 or 6 days after the thermal injury. With different efficacies time of action, the topical treatment with the Aloe saponaria cream (10%) and sulfadiazine (1%) decreased nociception, edema and leukocyte infiltration in animals induced by either thermal injury scald burn), or by UVB radiation. Moreover, the treatment with A. saponaria reduced the oxidative stress of the skin of animals irradiated with UVB, an effect that appears to be due to the antioxidant action produced by both the extract of A. saponaria, and by some of these constituents (rutin and aloin). Thus, our results demonstrate that topical application of A. saponaria showed antinociceptive, anti-inflammatory and antioxidant models of thermal injury (scald burn or solar radiation), which confirms the benefits of its traditional use for burn injuries effects.